Automated shopping list generator - Nor Izatie, Mohamad Nadry (2015)
Automated shopping list generator is an application that can give everyone especially for housewife to get the list of their needs systematically. This project is basically use platform like android Phone, Windows Phone and android. This system is easier to used, this system is not like an online shopping because I really focused on the items that is storage in freezer only. So, the foods are cannot be sell in online shopping. This system also only can be use for update the needs that people always use in cooking, like vegetable, fish, meat, chicken and others. Busy person sometimes cannot remember and they were not concern about their needs. This system will help them to be systematically in manage their work and warning message will be displayed if the food is finished. The items that users were brought will save in database, then the data can sync to other person that they want to sharing by install some application in their phone.